1982
DOI: 10.1038/clpt.1982.144
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of steady-state verapamil plasma concentrations in children and adults

Abstract: With data on adults from two previous articles it was found that the average steady-state plasma concentration of verapamil in subjects on long-term oral therapy of 80 mg every 6 hr (Y) correlated strongly with the area under the curve from zero to infinity (AUC0-x/6 (X) where the area refers to that for a single oral dose of 80 mg (Y - 2.41X, n - 15, r - 0.923, P less than 0.001). Steady-state concentrations are predictable from the single-dose data, with an average absolute deviation of 11.1%. We gave seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In contrast to several recent reports documenting substantial increases in verapamil half-life (Freedman et al 1981;Schwartz et al 1982bSchwartz et al , 1985Shand et al 1981), no increase in elimination half-life was observed by Eichelbaum and Somogyi (1984b) during long term dosing. Substantial inter-and intraindividual variations in morning trough and Anderson et al (1982) 3.43 ± 0.54 Freedman et al (1981) 5.04 ± 2.95 Wagner et al (1982) 9.17 ± 2.98 Somogyi et al (1981) Mooy et al (1985) Abbreviations: Cma• = maximum plasma concentration; tm8• = time of occurrence of Cma. ; CL" = apparent oral clearance; F = bioavailability; SVT = supraventricular tachyarrhythmias.…”
Section: Pharmacokinetics and Bioavailability During Multiple Dose Admentioning
confidence: 98%
“…In contrast to several recent reports documenting substantial increases in verapamil half-life (Freedman et al 1981;Schwartz et al 1982bSchwartz et al , 1985Shand et al 1981), no increase in elimination half-life was observed by Eichelbaum and Somogyi (1984b) during long term dosing. Substantial inter-and intraindividual variations in morning trough and Anderson et al (1982) 3.43 ± 0.54 Freedman et al (1981) 5.04 ± 2.95 Wagner et al (1982) 9.17 ± 2.98 Somogyi et al (1981) Mooy et al (1985) Abbreviations: Cma• = maximum plasma concentration; tm8• = time of occurrence of Cma. ; CL" = apparent oral clearance; F = bioavailability; SVT = supraventricular tachyarrhythmias.…”
Section: Pharmacokinetics and Bioavailability During Multiple Dose Admentioning
confidence: 98%
“…An infusion of 0.005 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 verapamil was started 3 minutes later and continued until the protocol was completed. [11][12][13][14] The mean total verapamil dosage was 16.4Ϯ2.8 mg administered over 27.4Ϯ3.5 minutes. In these 6 patients, the post-AF sinus cycle length (785Ϯ109 ms) and atrial-His interval (96Ϯ27 ms) were the same as or longer than before verapamil (sinus cycle length, 735Ϯ79 ms, Pϭ0.10; atrial-His interval, 87Ϯ15 ms, Pϭ0.02).…”
Section: Study Protocolmentioning
confidence: 99%
“…Equation (19) indicates that a plot of 1nF versus R will yield a straight line with intercept equal to -V Y K Z corresponding to R = 0, and F = 1 or In F = 0 when R = VZ. Figure 1 presents such a plot based on the verapamil parameter values in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Once values of V:, KZ, and Q are estimated for a given drug in a given subject one can construct a plot showing the dependency of systemic availability on dose rate using equation (19) based on the sinusoidal perfusion model. Equation (19) indicates that a plot of 1nF versus R will yield a straight line with intercept equal to -V Y K Z corresponding to R = 0, and F = 1 or In F = 0 when R = VZ. Figure 1 presents such a plot based on the verapamil parameter values in Table 1.…”
Section: Resultsmentioning
confidence: 99%